Incidencia del carbón del maní en nuevas zonas productivas - Asinari, Florencia; Monguillot, Joaquín Humberto; Morichetti, S.; Paredes, Juan Andrés; Perez, Ignacio Agustin; Rago, Alejandro Mario (2021)
Poster